Некоторые аспекты причины выселения и депортации народов - Калыбекова, М.Ч. (Изд-во КарГУ, 2010)
Сталиндік репрессия кезінде Қазақстанға бұрынғы Кеңес Одағының əр аймағынан зорлық-зомбылықпен əр ұлттардың өкілдері мен топтары көшіріліп, оларға фашистік Германиямен іштей байланыс жасады деген айып тағылды, олар 50-ші жылдардың ортасына дейін ерекше режимдік бақылауда болды. The representatives of various stratum of the population and also whole peoples and the ethnic groups was violently moved from different regions of former the USSR to Kazakhstan during Stalin repression’s. Communists accused them in cooperation with fascist Germany and almost up to middle 1950 years these people were under a special mode.
Keywords: 1-ая половина XX века; Советский Союз; история; политическая система; депортация народов; население; массовое переселение; Средняя Азия; Казахстан; чеченские переселенцы